The role of data visualization in auditing: a systematic literature review - Muhammad Alam Mauludina; Sri Mulyani; Srihadi Winarningsih; Hendra Susanto (Cogent Business & Management, 2024)
The study aims to systematically review the role of big data visualization in the auditing field. Employing a qualitative approach, the research utilized the Systematic Literature Review method to gather pertinent data. The study used 35 published articles extracted from different journals and reputed publishers, which served as the sample. This research provides an overview of the data visualization trend literature in auditing and describes the associated capabilities and practices. The result showed a fluctuating pattern in the publication years, highlighting a relatively recent research area, with the highest volume noted in 2021. The findings indicated that most articles used qualitative methods, such as conceptual or case study research. This suggests that empirical research is needed to add to the body of knowledge of data visualization in auditing. Furthermore, the study identified nine of the main capabilities of data visualization to improve audit quality. The study offers valuable perspectives for both practitioners and researchers, detailing the progress made to date and identifying future avenues of inquiry within the discipline. The study contributes to extending the literature on accounting information systems and auditing and provides a knowledge gap for further analysis.
Keywords: 650; Big data; data visualization; data analytics; audit; systematic literature review